Terminal digit preference biases polyp size measurements at endoscopy, computed tomographic colonography, and histopathology - Plumb, Andrew A.; Nickerson, Claire; Wooldrage, Katherine; Bassett, Paul; Taylor, Stuart A.; Altman, Douglas; Atkin, Wendy; Halligan, Steve (Endoscopy, 2016)
Background and study aims: Terminal digit preference bias for “pleasing” numbers has been described in many areas of medicine. The aim of this study was to determine whether endoscopists, radiologists, and pathologists exhibit such bias when measuring colorectal polyp diameters.Methods: Colorectal polyp diameters measured at endoscopy, computed tomographic colonography (CTC), and histopathology were collated from a colorectal cancer screening program and two parallel multicenter randomized trials. Smoothing models were fitted to the data to estimate the expected number of polyps at 1-mm increments, assuming no systematic measurement bias. The difference between the expected and observed numbers of polyps was calculated for each terminal digit using statistical modeling. The impact of measurement bias on per-patient detection rates of polyps ≥ 10 mm was estimated for each modality. Results: A total of 92 124 individual polyps were measured by endoscopy (91 670 screening and 454 from trials), 2385 polyps were measured by CTC (1664 screening, 721 trials), and 79 272 were measured by histopathology (78 783 screening, 489 trials). Clustering of polyp diameter measurements at 5-mm intervals was demonstrated for all modalities, both in the screening program and the trials. The statistical models estimated that per-patient detection rates of polyps ≥ 10 mm were over-inflated by 2.4 % for endoscopy, 3.1 % for CTC, and 3.3 % for histopathology in the screening program, with similar trends in the randomized trials.Conclusion: Endoscopists, radiologists, and pathologists all exhibit terminal digit preference when measuring colorectal polyps. This will bias trial data, referral rates for further testing, adenoma surveillance regimens, and comparisons between tests.